Establishing a quantitative fluorescence assay for the rapid detection of kynurenine in urine. Issue 9 (7th April 2022) - Patel, Kamlesh; Fernandez-Villamarin, Marcos; Ward, Craig; Lord, Janet M.; Tino, Peter; Mendes, Paula M.
Abstract : A fluorescence-based assay for the detection of kynurenine in urine for low-cost and high-throughput analysis in clinical laboratory settings. Abstract : The kynurenine metabolite is associated with many diseases and disorders, ranging from diabetes and sepsis to more recently COVID-19. Here we report a fluorescence-based assay for the detection of kynurenine in urine using a specific chemosensor, 3-formyl-4-(ethylthio)-7-(diethylamino)-coumarin. The assay produces a linear response at clinically relevant ranges (1–20 μM), with a limit of detection of 0.7 μM. The average standard addition recoveries of kynurenine in synthetic urine samples are near to 100%, and the relative standard deviation values are less than 8%. The established fluorescence assay for quantitative analysis of kynurenine in urine is facile, sensitive and accurate and holds great potential for low-cost and high-throughput analysis of kynurenine in clinical laboratory settings.